2016
DOI: 10.1155/2016/4574673
|View full text |Cite
|
Sign up to set email alerts
|

Regional Odontodysplasia with Generalised Enamel Defect

Abstract: Regional odontodysplasia (ROD) is uncommon developmental anomaly, which tends to be localised and involves the ectodermal and mesodermal tooth components. A five-year-old female was referred to Department of Child Dental Health at the Leeds Dental Institute regarding malformed primary teeth. On examination 64, 74, and 72 had localised hypomineralized enamel defect. The crown of 55 was broken down with only the root remaining below the gingival level. 54 has a yellowish brown discolouration with rough irregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 24 publications
1
13
0
3
Order By: Relevance
“…Walton et al (1978) proposed that local disturbance of vascular supply produces a localized ischemia that disturbs odontogenesis. Another interesting finding was reported in a 5-year-old girl which presented with generalized enamel defects in the primary dentition in addition to regional odontodysplasia (Al-Mullahi and Toumba, 2016). Although generalized enamel defects in primary teeth of healthy children are relatively common (Robles et al, 2013), the authors did not present any investigations to correlate between those concomitant conditions.…”
Section: Discussionmentioning
confidence: 77%
“…Walton et al (1978) proposed that local disturbance of vascular supply produces a localized ischemia that disturbs odontogenesis. Another interesting finding was reported in a 5-year-old girl which presented with generalized enamel defects in the primary dentition in addition to regional odontodysplasia (Al-Mullahi and Toumba, 2016). Although generalized enamel defects in primary teeth of healthy children are relatively common (Robles et al, 2013), the authors did not present any investigations to correlate between those concomitant conditions.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, both genders were almost equally affected which is interesting since females should be affected more than males. Moreover, the review of the literature showed that most authors recommend extraction of the affected teeth, few authors prefer the conservative approach, while only two studies used autotransplantation of structurally sound teeth into the affected area . Nevertheless, between the conservative approach and the radicular approach, the regenerative approach has never been used.…”
Section: Discussionmentioning
confidence: 99%
“…It affects a specific segment in either/both dentitions in the either/both jaws. It is suggested that ROD affects females more than males but does not affect any particular ethnic group more than others . ROD usually affects the maxilla twice as often as the mandible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors causing OR have been mentioned, such as neural crest cell defects, viral infections, local trauma, Rh incompatibility, hyperpyrexia, ionizing radiation, teratogenic pharmacological agents and nutritional and/or metabolic alterations. OR has been associated with the presence of nevus, hypophosphatasia, hypocalcaemia, ectodermal dysplasia, and hydrocephalus; however, most cases of OR are not associated with medical alterations [9,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%